Persistent postconcussive symptoms in children and adolescents with mild traumatic brain injury receiving initial head computed tomography - Riemann, Lennart; Voormolen, Daphne C.; Rauen, Katrin; Zweckberger, Klaus; Unterberg, Andreas; Younsi, Alexander (Journal of neurosurgery. Pediatrics, 2021)
The aim of this paper was to evaluate the prevalence of postconcussive symptoms and their relation to health-related quality of life (HRQOL) in pediatric and adolescent patients with mild traumatic brain injury (mTBI) who received head CT imaging during initial assessment. METHODS Patients aged between 5 and 21 years with mTBI (Glasgow Coma Scale scores 13-15) and available Rivermead Post Concussion Questionnaire (RPQ) at 6 months of follow-up in the multicenter, prospectively collected CENTER-TBI (Collaborative European NeuroTrauma Effectiveness Research in TBI) study were included. The prevalence of postconcussive symptoms was assessed, and the occurrence of postconcussive syndrome (PSC) based on the ICD-10 criteria, was analyzed. HRQOL was compared in patients with and without PCS using the Quality of Life after Brain Injury (QOLIBRI) questionnaire. RESULTS A total of 196 adolescent or pediatric mTBI patients requiring head CT imaging were included. High-energy trauma was prevalent in more than half of cases (54%), abnormalities on head CT scans were detected in 41%, and admission to the regular ward or intensive care unit was necessary in 78%. Six months postinjury, 36% of included patients had experienced at least one moderate or severe symptom on the RPQ. PCS was present in 13% of adolescents and children when considering symptoms of at least moderate severity, and those patients had significantly lower QOLIBRI total scores, indicating lower HRQOL, compared with young patients without PCS (57 vs 83 points, p < 0.001). CONCLUSIONS Adolescent and pediatric mTBI patients requiring head CT imaging show signs of increased trauma severity. Postconcussive symptoms are present in up to one-third of those patients, and PCS can be diagnosed in 13% 6 months after injury. Moreover, PCS is significantly associated with decreased HRQOL.